Proceedings of the Computing Frontiers Conference 2017
DOI: 10.1145/3075564.3075589
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Workload Prediction by Means of Simulations

Abstract: Clouds hide the complexity of maintaining a physical infrastructure with a disadvantage: they also hide their internal workings. Should users need to know about these details e.g., to increase the reliability or performance of their applications, they would need to detect slight behavioural changes in the underlying system. Existing solutions for such purposes o er limited capabilities. is paper proposes a technique for predicting background workload by means of simulations that are providing knowledge of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…The results represented that the model accuracy is up to 91%, with efficiency in resource usage and maintaining the QoS. Kecskemeti et al suggested a workload prediction method using simulations, which provides the knowledge of the underlying clouds to support activities such as cloud orchestration or workflow enactment.…”
Section: Related Workmentioning
confidence: 99%
“…The results represented that the model accuracy is up to 91%, with efficiency in resource usage and maintaining the QoS. Kecskemeti et al suggested a workload prediction method using simulations, which provides the knowledge of the underlying clouds to support activities such as cloud orchestration or workflow enactment.…”
Section: Related Workmentioning
confidence: 99%
“…Many studies have been conducted on various predictions in cloud computing. From the perspective of research objectives, some researchers have studied server load prediction [ [6][7][8][9][10], VM load prediction [11,12], VM utilization prediction [13,14], host utilization prediction [15], web application workload prediction [16], cloud service workload prediction [17][18][19], workflow workload prediction [20], service quality prediction [21], and workload characterization [22][23][24]. Toumi et al [6] described a server load according to the submitted task types and the submission rate and applied a stream mining technique to predict server loads.…”
Section: Related Workmentioning
confidence: 99%